EXPLORING THE DYNAMICS OF AN EXOTHERMIC CHEMICAL REACTION CONTROLLED BY ARRHENIUS KINETICS WITH HALL EFFECT IN A MICROCHANNEL - Hamza, M. M.; Ahmad, S. K.; Ojemeri, Godwin; Usman, H.; Shuaibu, A. (FUDMA JOURNAL OF SCIENCES, 2023)
The consequences of chemically reactive fluids have provoked many researchers due to their potential to enhance the behavior of heat. Hence, this article discussed a theoretical investigation to explore the actions of Arrhenius chemical reaction and Hall current on hydro-magnetic free convection of a viscous fluid flowing along an upstanding micro-channel. Subject to the required boundary conditions, the governing coupled equations representing the flow pattern in non-dimensional form were solved using the homotopy perturbation method (HPM). Line graphs are also used to generate expressions for energy, momentum, volume flow rate, drag force, and Nusselt number in both primary and secondary flow directions as a function of regulating parameters like chemical reaction, Hall current, rarefaction, and wall ambient temperature difference ratio. It is worthy of note that the fluid temperature and the fluid flow are substantially propelled by the viscous heating term in the Arrhenius chemical reaction of the system for growing values of the wall ambient temperature difference ratio parameter. Additionally, it is noticeable that volume flow rate performance is seen as a growing influence of viscous heating and rarefaction parameters. The findings of this study can be applied to a wide range of electrically controlled devices, thermal and petro chemical engineering, and the serviceability of industrial products.
Keywords: Hall effect; Arrhenius kinetics; Rarefaction; Micro-channel; Homotopy perturbation method (HPM)